The Role of Capital Structure, Human Resources, and Technology in Increasing Salt Farmers’ Income - Wulandari, Vitri; Yunus, Mahmud; Eka Prastya Nugraha, Aryan; Purnomo Adhi, Antono Herry (SOCA: Jurnal Sosial Ekonomi Pertanian, 2021)
The natural resources of hot salty springs can be used by farmers to produce salt. The salt farmer profession has not provided an economic improvement for the farmers themselves. The purpose of this study was to determine the role of capital structure, human resources and technology in increasing the income of salt farmers in Jono Village. The research method used in this study was qualitative descriptive approach. The data of this study were obtained from interviews, observations and documents. Data analysis usedin this study was an interactive model from Miles and Huberman, 2014. The study was carried out in Jono Village, Tawangharjo District, Grobogan Regency. The results of this study are the capital structure of salt farmers obtained from collectors and human resources from family labor which are still low. The technology used by salt farmers is still very traditional. The results of this study provide recommendations for improving the capital structure, quality of capital resources and technology to improve the economy of the salt farmers.